Educação e Literatura: Voltaire e a função educadora dos textos literários - Santana, Christine Ardnt de (2008)
What we have in mind in this thesis is to understand and identify the literature educational role in French Illustration, known as the intellectual movement of XVIII century. The specific goals of this research are: understand some literary expressions - the pamphlet, the short story, for example - as instruments in service of education, considering that they are effective when transmitting moral values and, at last, showing how the educational function of literature in Voltaire is achieved, through the analysis of his short stories. To succeed in researching these goals, the text was divided in three chapters. The first, called "Illustration, Education and Literature", exposes the context of the historical period studied, presenting some of its main characteristics, through Voltaire's writings and, after, through modern and illustrative movement commentators; after this exposure, it discussed, in short words, the transformation that happened with pedagogy in that time. The second chapter, "Voltaire - Illustration and militant work", started pointing, yet, some changes that happened in Modern era to, after, present Voltaire and his epoch, focusing in the influence of this author and the revolution that this influence generated; Voltaire's works analyzed in this moment of the thesis, in order to observe the revolution and influence of the philosopher, are: Memórias, Dicionário Filosófico, Cartas Filosóficas, Tratado sobre a Tolerância, Tratado de Metafísica and O Filósofo Ignorante. Finally, the third chapter, named "Voltaire and the 'moral in action'", the main part of the thesis, and brings, in its lines, the literary theory that based the theme of this investigation, to know, the educational function of literary texts; in that sense, it was very important to the understanding of the proposed problem, the analysis of Voltaire's short story, called Jeannot e Colin, to illustrate how the literary pedagogical function is processed.